Developing Computational Thinking Skills Through Modeling in Language Lessons - Rottenhofer Marina; Sabitzer Barbara; Rankin Thomas (De Gruyter, 2021)
Technology is rapidly changing the world around us and thus, there is a need to adjust education by teaching children skills that are required in the fast-paced digital life. One problem-solving skillset, which has gained considerable attention in the last couple of years, is computational thinking (CT). Up to now, many countries have already implemented CT as an integral part of their education curricula, however, there is still often the misconception that teaching CT requires high technical effort and profound knowledge of computer science. Whereas CT is useful in any subject, it is not necessarily linked to technology and helps children to tackle problems by applying skills that are used in computer science. One effective hands-on approach to foster CT in every subject is modeling. A model is a simplified and reduced version of the real world and modeling is the process of creating it. In this paper, the authors focus on fostering CT skills with models from the field of computer science (CS) in foreign language teaching. The authors present several CS models, that have proven to be useful in language teaching, demonstrate how this approach can foster CT skills and give an insight into their research.